2010
DOI: 10.1080/15388220.2010.508133
|View full text |Cite
|
Sign up to set email alerts
|

How Safe Is a School? An Exploratory Study Comparing Measures and Perceptions of Safety

Abstract: This exploratory study investigates the relation between incident reports to local law enforcement, and students' and teachers' perceptions of school safety. Using a combination of grounded theory and statistics, we compared quantitative data collected from law enforcement agencies with qualitative data provided by students and teachers during focus groups. Findings show that incidents of serious violence and attacks, minor violence, and other school-related crime, in that order, constituted the most frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Hence, both boys and girls can commit more verbal aggressions because these are mixed up with tricks or ordeals typical of the age. 29 In view of the results found on the emotions produced in the context of bullying, the most prevailing response among the male and female victims was anger. Although the information on how the emotional conditions of children and adolescents in bullying situations are related to their reaction towards the aggression remain limited, it is clear that the emotions can function as catalysts of this process, stimulating more or less appropriate reactions to cope with the violence.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, both boys and girls can commit more verbal aggressions because these are mixed up with tricks or ordeals typical of the age. 29 In view of the results found on the emotions produced in the context of bullying, the most prevailing response among the male and female victims was anger. Although the information on how the emotional conditions of children and adolescents in bullying situations are related to their reaction towards the aggression remain limited, it is clear that the emotions can function as catalysts of this process, stimulating more or less appropriate reactions to cope with the violence.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between teacher and student perceptions of school safety also exist, with teachers tending to rate schools safer than students (see also Booren, Handy, & Power, 2011). However, Hernandez and colleagues (Hernandez, Floden, & Bosworth, 2010) found that although students and teachers shared comparable perceptions of safety, these did not necessarily correspond with law enforcement reports. Other aspects of the school environment such as teaching involvement and school rule enforcement increased opinions of safety, while the reverse effect was evident for observed weapon carrying, actual or perceived levels of victimization, larger class sizes, and school disorder (Hong & Eamon, 2012;Melde & Esbensen, 2009;Perumean-Chaney & Sutton, 2013).…”
Section: Perceptions Of School Safetymentioning
confidence: 99%
“…Firstly, the participants conducted the study within a framework of legal legislation in order to create content related to their own specific subject areas. Despite the existence of legislation, there have been notable information and perception deficiencies in its implementation (Çalık et al, 2018;Hernandez et al, 2010). For this reason, integrating appropriate content into the materials design and construction was an important area of critique, which was successfully achieved by the preservice teachers.…”
Section: Discussionmentioning
confidence: 99%